The Meaning of Hijab: Fashion or Religious Identity? A Study on Young Consumers of Hijab in Indonesia - Yuliana, Ade; Sukoco, Hendro (Indonesian Journal of Islamic Business and Economics (IJIBE), 2025)
This research examines the influence of religiosity, fashion consciousness, and social influence on the intention to wear the hijab among young Muslim women in Indonesia. Using the Theory of Planned Behavior (Ajzen, 1991) as the theoretical framework, this research explores how internal and external factors shape hijab-wearing behavior that has evolved from a purely religious obligation to a cultural and fashion statement. A quantitative survey was conducted involving 130 respondents in Purwokerto, with data analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that religiosity (β = 0.664), fashion consciousness (β = 0.409), and social influence (β = 0.597) all have a positive and significant effect on the intention to wear the hijab. Religiosity emerged as the most dominant factor, indicating that spiritual values remain central in shaping women’s dressing intentions despite the growing influence of fashion and social trends. These results contribute to consumer behavior literature in the context of identity-based products, highlighting the coexistence of religious commitment and modern lifestyle. Practically, the study offers insights for hijab fashion marketers to integrate Sharia compliance with contemporary design and leverage social influence through digital and community-based marketing strategies